Wearable EMI Shielding Composite Films with Integrated Optimization of Electrical Safety, Biosafety and Thermal Safety - Liang Li; Yongzhu Yan; Jufu Liang; Jinchuan Zhao; Chaoyi Lyu; Haoxiang Zhai; Xilong Wu; Guizhen Wang (Advanced Science, 2024)
Abstract Biomaterial‐based flexible electromagnetic interference (EMI) shielding composite films are desirable in many applications of wearable electronic devices. However, much research focuses on improving the EMI shielding performance of materials, while optimizing the comprehensive safety of wearable EMI shielding materials has been neglected. Herein, wearable cellulose nanofiber@boron nitride nanosheet/silver nanowire/bacterial cellulose (CNF@BNNS/AgNW/BC) EMI shielding composite films with sandwich structure are fabricated via a simple sequential vacuum filtration method. For the first time, the electrical safety, biosafety, and thermal safety of EMI shielding materials are optimized integratedly. Since both sides of the sandwich structure contain CNF and BC electrical insulation layers, the CNF@BNNS/AgNW/BC composite films exhibit excellent electrical safety. Furthermore, benefiting from the AgNW conductive networks in the middle layer, the CNF@BNNS/AgNW/BC exhibit excellent EMI shielding effectiveness of 49.95 dB and ultra‐fast response Joule heating performance. More importantly, the antibacterial property of AgNW ensures the biosafety of the composite films. Meanwhile, the AgNW and the CNF@BNNS layers synergistically enhance the thermal conductivity of the CNF@BNNS/AgNW/BC composite film, reaching a high value of 8.85 W m‒1 K‒1, which significantly enhances its thermal safety when used in miniaturized electronic device. This work offers new ideas for fabricating biomaterial‐based EMI shielding composite films with high comprehensive safety.